1991
DOI: 10.1111/j.1472-8206.1991.tb00726.x
|View full text |Cite
|
Sign up to set email alerts
|

The uterotonic action of the aqueous extract of Bridelia atroviridis in the rat

Abstract: The effects of the aqueous extract of leaves of Bridelia atroviridis (Bridelia), a small African tree, on the mechanical activity of rat uterus were studied. The aqueous extract of leaves of B atroviridis administered in a concentration-dependent manner (5 x 10(-6)-1.2 x 10(-3) g/ml) induced contractions that were antagonized by various calcium entry blockers (nifedipine, diltiazem, manganese chloride). In absence of external calcium ions, repeated applications of a supramaximal concentration of Bridelia (1.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…41,125,[198][199][200][201][202][203][204][205][206][207][208] It has been demonstrated by Agarwal et al 209 that two species of Phyllanthus, P. emblica, and P. niruri, were effective in antagonizing the clastogenic effect induced by nickel chloride in mouse bone marrow cells. Suresh and Vasudevan 201 demonstrated that P. emblica enhanced the natural killer-cell activity and antibody-dependent cellular cytotoxicity in syngeneic BALB/c mice bearing Daltom's lymphoma ascites tumor.…”
Section: O T H E R P H a R M A C O L O G I C A L E F F E C T S R E P mentioning
confidence: 99%
“…41,125,[198][199][200][201][202][203][204][205][206][207][208] It has been demonstrated by Agarwal et al 209 that two species of Phyllanthus, P. emblica, and P. niruri, were effective in antagonizing the clastogenic effect induced by nickel chloride in mouse bone marrow cells. Suresh and Vasudevan 201 demonstrated that P. emblica enhanced the natural killer-cell activity and antibody-dependent cellular cytotoxicity in syngeneic BALB/c mice bearing Daltom's lymphoma ascites tumor.…”
Section: O T H E R P H a R M A C O L O G I C A L E F F E C T S R E P mentioning
confidence: 99%
“…308 Aqueous extract of the leaves of B. atroviridis administered in a concentration-dependent manner Handbook of african Medicinal Plants induced contractions on rat uterus that were antagonized by various calcium entry blockers. 316 The cellular basis for the uterotonic activity of the plant extract appeared to be complex and probably involves mechanisms including calcium mobilization from both intra-and extracellular compartments and activation of phospholipase C through a G-protein. 316 The β-amyrin-rich extracts of B. ferruginea leaves possess antioxidant and cytotoxic activities.…”
Section: Synonyms -Gentillia Chevalieri Beillementioning
confidence: 99%
“…316 The cellular basis for the uterotonic activity of the plant extract appeared to be complex and probably involves mechanisms including calcium mobilization from both intra-and extracellular compartments and activation of phospholipase C through a G-protein. 316 The β-amyrin-rich extracts of B. ferruginea leaves possess antioxidant and cytotoxic activities. 317 Intraperitoneal administration of aqueous extract of B. ferruginea at the dose of 10 mg/kg produced a significant increase in urinary excretion of creatinine (p < 0.01 compared to a control) and creatinine clearance in rats.…”
Section: Synonyms -Gentillia Chevalieri Beillementioning
confidence: 99%